(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article is dedicated to the study of the immune system and its role in protecting the body from infections. It examines the key mechanisms of innate and adaptive immunity, as well as the historical development of methods for the prevention and treatment of infectious diseases since the early 20th century.